Nurses' perceptions toward seclusion and use of restraints for psychiatric patients in Greece - Lemonidou, Chryssoula; Priami, Maria; Merkouris, Anastasios; Kalafati, Maria; Tafas, Cheryl; Plati, Chryssanthi (My University, 2002)
The purpose was to: a) investigate the type of restriction used to suppress violent behaviour of psychiatric patients, b) explore nurse's attitudes toward seclusion and restraints, and c) determine if there is a difference in nurse's attitudes due to their level of education and years of experience. Method: The sample consisted of 190 nurses working in psychiatric wards. The study was conducted in 12 psychiatric wards of five hospitals. A self-administered questionnaire was distributed and statistical analysis was done using descriptive statistics and chi-square test. Results: The most frequently reported restraints included body restriction (42.6%), room isolation (26%), and both (31.1%). The seclusion or restraints are used most often for patient safety (70.5%), behaviour control (23.2%), and for staff convenience (0.5%). Eighty percent of nurses favour restraints, while 16.8% are against. There were no statistically significant differences in nurses' attitudes due to their level of education, or work experience.
Keywords: Europe; Human; Greece; Public health; Mental health; Attitude; Professional experience; Education level; Health staff; Violence; Mental disorder; Seclusion unit; Use; Judgment; Psychiatric nurse